The Health Determinants of Accessibility to Clubfoot Treatment in LMICs: A Global Exploration of Barriers and Solutions - Sharaf Sheik-Ali; Sergio M Navarro; Evan J Keil; Evan Keil; Walter Johnson; Chris Lavy (Global Health and Education Projects, Inc., 2021)
Background: Clubfoot or Congenital Talipes Equinovarus (CTEV) treatment in newborn infants involves simple, non-invasive manipulation and is primarily managed non-surgically if identified early. In low- and middle-income countries (LMICs), less than 15% of patients with CTEV access treatment. This cross-sectional questionnaire study conducted descriptive and regression analysis of institutional reasons for CTEV management in LMICs. Methods: A cross-sectional study was undertaken of 1,489 medical institutions in 62 LMICs. Data were evaluated from the "World Health Organization Situation Analysis tool" database. We analyzed characteristics of institutions that manage and did not manage CTEV. With the use of a multivariate linear regression model, we identified a set of factors linked to referral for non-management of CTEV. Results: A total of 72.7% (1,083/1,395) of institutions surveyed did not manage CTEV. The most common reason cited for not managing CTEV was a lack of sufficient skills, 92.1% (668/725, P<0.001). A total of 39.4% (286/725) of institutions also cited a lack of functioning equipment as a reason. Multivariate linear regression analysis showed lack of training, lack of supplies, and lack of functioning equipment were most closely related to non-management of CTEV. Conclusion and Global Health Implications: We identified that failure to manage CTEV may result from a lack of skills and medical equipment. Increasing the capacity of sustainable training programs may reduce the presently available skill deficit in treating CTEV in LMICs and provide improved health outcomes for those with CTEV. While considerable progress has been made in building capacity for the treatment and management of CTEV in LMICs, structured training programs that support conservative manipulative methods to manage CTEV should be initiated globally.   Copyright © 2021 Sheik-Ali et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0.